Ketentuan Pengaturan Penteraan Alat Metrologi Legal dalam Transaksi Perdagangan di Indonesia - Ilka Sandela; Nila Trisna; Dara Quthni Effida (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
Legal metrology tools such as measuring instruments, measurements, scales and equipment used in trade transactions must be calibrated and recalibrated within a certain period of time. The goal is the measurement results using these tools remain correct as they should be. If it is not calibrated or recalibrated, it can cause measurements to be inaccurate, so that it can be detrimental to consumers in trade. This study aims to study further on the regulation of calibration of legal metrology equipment, sanctions, mechanisms or procedures for calibration and recalibration. The research method used is a normative juridical research method. The results of the study indicate that the provisions relating to the calibration of legal metrology equipment consisting of measuring, weighing and complete instruments are regulated in Law Number 2 of 1981 concerning Legal Metrology and Government Regulation Number 2 of 1985 concerning mandatory and free to be calibrated and/or or recalibration for measuring, weighing instruments and their accessories. In this provision, it is determined that there is an obligation to calibrate and recalibrate measuring, and weighing instruments used for public purposes, business purposes, the need for delivery and receipt of goods, determination of the company's final product, mandatory calibration and recalibration. As for the sanctions for business actors who commit acts prohibited by the Legal Metrology Law, they are subject to criminal sanctions in the form of imprisonment for a maximum of 1 (one) year and a fine of a maximum of Rp. 1,000,000 (one million rupiah). Furthermore, the mechanism or procedure for calibration of legal metrology tools includes the owner or user of measuring instruments, measuring, weighing in a clean condition, registering and paying calibration fees, then employees carry out inspections and tests, then the results are posted.